Condenser Optimization in Steam Power Plant - Bekdemmir, Sukru; Ozturk, Recep; Yumurtac, Zehra (SPRINGER, 2003)
In this paper the effects of the condenser design parameters (such as turbine inlet condition, turbine power and condenser pressure) on heat transfer area, cooling water flow-rate, condenser cost and specific energy generation cost are studied for surface type condenser. The results are given in the text and also shown as diagrams.
Keywords: condensers; steam power plants; energy cost; Thermodynamics; Engineering